Cúbicas Reversas e Redes de Quádricas - Freire, Ageu Barbosa (2016)
In this work, we present an explicit geometric characterization for the space of quadratcs form vanishing precisely on a twisted cubic. We show that the set of degenerate quadrics lying on a net of quadrics containing a twisted cubic is described by a curve whose equation is given by the square of an irreducible conic. Conversely, if is a net of quadrics whosw intersection with the set of degenerate quadrics is a curve given by the square of an irreducible conic, we furnish conditions under which the cammon zero locus of turns out to be a twisted cubic. It is enough to require that does not contain a pair of planes.